INCIDENCE OF PRESSURE ULCERS ON HOSPITALIZED PATIENTS: LITERATURE REVIEW (Fiep Bulletin - online, 2014)
The pressure ulcers (PU) are considered chronic wounds, from areas submitted to a constant ischemic process and, consequently, tissue death, which presence in institutionalized patients is a parameter for assistance evaluation. In the United States, around 2.1 million patients develop PU per year. in Europe, Canada and South Africa, from 3% to 11% of hospitalized patients present PU. In Brazil, studies on the PU occurrence in critical patients are few and only consider the assessment of the PU presence, while the patient is in the ICU. This study was designed to conduct a literature review on the incidence of pressure ulcers in hospitalized patients in the LILACS database, between 2000 and 2006. So, a research was developed in scientific articles papers until until october/2007, being used as descriptors: “pressure ulcer” and “incidence”. According to the scientific articles searched, we can observe that the general incidence ranged from 1.0% to 55.6%, being the major indexes identified in patients with marrow injury. As for the sedated and not sedated patients, an article researched showed statistically significant difference (p-value = 0.0323). In the case of patients assisted by an assistance protocol, there was a low incidence (3.7%), justifying the fundamental importance of systematic protocols implementation for evaluation the risk of PU development. According to the scientific articles searched, we can observe that the hospital general incidence ranged from 1.0% to 55.6%, being higher in ICU (7.2% to 41.1%). The major indexes were identified in patients with marrow injury, ranging from 42.5% to 55.6%, showing that the impaired mobility is a major risk factor for PU.
Keywords: Pressure Ulcer; Incidence; Hospital